Comparing and Evaluating Five-Day Chemotherapy Agents Actinomycin D and Methotrexate in Low-Risk Post-Molar Gestational Trophoblastic Neoplasia: A Retrospective Analysis - Juan Xu; Xinmei Wang; Pengpeng Qu (Clinical and Experimental Obstetrics & Gynecology)
Background: Low-risk post-molar gestational trophoblastic neoplasia is sensitive to chemotherapy, but there is no consensus regarding the best treatment regimen for low-risk post-molar gestational trophoblastic neoplasia. This study aimed to assess the efficacy, toxicity and cost-effectiveness of actinomycin D and methotrexate in low-risk post-molar gestational trophoblastic neoplasia. Methods: 210 patients with Federation International of Gynecology and Obstetrics(FIGO)-defined low-risk post-molar gestational trophoblastic neoplasia received either a first-line five-day methotrexate intramuscular injection biweekly (MTX group) or a five-day actinomycin D infusion biweekly (Act-D group). Demographic information, disease manifestations, initial treatment plan, treatment-related adverse events, cost-effectiveness and the effects of drugs on ovarian function and quality of sexual life were recorded and retrospectively compared. Results: The complete response rates were 72.73% for the Act-D group and 75.41% for the MTX group, with no statistically significant difference. Compared to the Act-D group, the MTX group had a significantly shorter total number of chemotherapy cycles and average hospitalization expenses (p < 0.05). There was no severe adverse effect reported for either group, but the Act-D group was associated with significantly higher leukopenia (grade 1 or 2) (59.38% vs. 17.39%). The two regimens had reversible effects on ovarian function and quality of sexual life, but there was no significant difference between the two groups. Conclusions: There were similar complete response rates and no severe adverse effect reported for either group, but the total treatment course was shorter and the average hospitalization expenses were lower in the MTX group. Five-day MTX intramuscular biweekly injections remain the treatment of choice for patients with low-risk post-molar gestational trophoblastic neoplasia. Chemotherapy will have a certain impact on ovarian function. Gynecological oncologists should pay attention to the protection of ovarian function in patients with gestational trophoblastic neoplasia during perioperative chemotherapy.